2016
DOI: 10.1007/s40534-016-0117-3
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous vehicles: challenges, opportunities, and future implications for transportation policies

Abstract: This study investigates the challenges and opportunities pertaining to transportation policies that may arise as a result of emerging autonomous vehicle (AV) technologies. AV technologies can decrease the transportation cost and increase accessibility to low-income households and persons with mobility issues. This emerging technology also has far-reaching applications and implications beyond all current expectations. This paper provides a comprehensive review of the relevant literature and explores a broad spe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
252
0
4

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 576 publications
(300 citation statements)
references
References 77 publications
0
252
0
4
Order By: Relevance
“…Several studies have briefly discussed the benefits of AVs. These include reduced transportation cost (Bagloee et al, 2016), decreased crashes (Kyriakidis et al, 2015;Li et al, 2018), reduced fuel consumption (Kyriakidis et al, 2015;Li et al 2018), lowered traffic congestion Li et al, 2018), lowered driving stress (Buckley et al, 2018), enhanced critical mobility for elderly and disabled people (Litman, 2019), reduced vehicle ownership (Bagloee et al, 2016), easened parking (Nourinejad et al, 2018) and more efficient and smooth traffic circulation (Bagloee et al, 2016). While some benefitssuch as relieving driving stress and easened parkingare easily acceptable, others are debatable.…”
Section: Expected Benefits Of Avsmentioning
confidence: 99%
See 3 more Smart Citations
“…Several studies have briefly discussed the benefits of AVs. These include reduced transportation cost (Bagloee et al, 2016), decreased crashes (Kyriakidis et al, 2015;Li et al, 2018), reduced fuel consumption (Kyriakidis et al, 2015;Li et al 2018), lowered traffic congestion Li et al, 2018), lowered driving stress (Buckley et al, 2018), enhanced critical mobility for elderly and disabled people (Litman, 2019), reduced vehicle ownership (Bagloee et al, 2016), easened parking (Nourinejad et al, 2018) and more efficient and smooth traffic circulation (Bagloee et al, 2016). While some benefitssuch as relieving driving stress and easened parkingare easily acceptable, others are debatable.…”
Section: Expected Benefits Of Avsmentioning
confidence: 99%
“…It is also aligned with Kyriakidis et al (2015), whose extensive study across 109 countries also indicated similar results. In Bagloee et al (2016) too, system security and integrity emerged as a serious concern, due to which customers might be reluctant to use AVs. When customers perceive security and privacy to be wanting, their acceptance of AVs is likely to be low.…”
Section: Cld: Feedback Loopsmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, a high degree of mass mobilization for societal and individual well-being comes at a price. Such mobilization makes resource consumption, global warming, noise pollution, traffic congestion and traffic incidents increasingly common and extremely challenging problems for academia, industry, society and governments [1,2]. To mitigate these problems, electrification and intellectualization have become two parallel and frequently discussed topics for automobiles.…”
Section: Introductionmentioning
confidence: 99%